Accuracy Assessment of Static GNSS Positioning: A Comparison between Geodetic GNSS and Low-Cost Smartphone-Based GNSS Using Geo++ RINEX - Een Lujainatul Isnaini; Septa Eka Putri (Journal of Applied Geospatial Information, 2026)
The Global Navigation Satellite System (GNSS) has been widely applied in various positioning applications, ranging from navigation to high-precision geodetic surveying. Recent advances in smartphone technology have enabled the collection of raw GNSS observations using low-cost devices, offering an affordable alternative for positioning applications. One such solution is the Geo++ RINEX Logger application, which records raw GNSS observations in the Receiver Independent Exchange Format (RINEX) for post-processing. This study evaluates the positioning accuracy of a smartphone-based Geo++ RINEX Logger compared with a geodetic GNSS receiver using the static relative positioning method under different observation durations and processing approaches. Observations were conducted at the ITERA benchmark under open-sky conditions with observation durations of 5, 15, 30, 45, and 60 minutes and a 1-second sampling interval. The data were processed using commercial GNSS software (offline) and the BIG online processing service (nrtk.big.go.id) based on the WGS-84 datum. The results indicate that positioning precision improved with increasing observation duration, with the 60-minute observations producing the smallest standard deviations. Geo++ RINEX Logger achieved centimeter-to-decimeter precision but lower accuracy than the geodetic GNSS receiver due to the limitations of single-frequency observations and sensitivity to baseline length and satellite geometry. These findings demonstrate that Geo++ RINEX Logger is a promising low-cost solution for educational, practical, and non-high-precision surveying applications.